Implementasi PSAK 109 pada Akuntansi ZIS: Bukti Empiris dari BAZNAS Kediri, Indonesia: (PSAK 109 Implementation in ZIS Accounting: Evidence from BAZNAS Kediri, Indonesia) - Suprihantosa Sugiarto; Fani Ma’sumatul Maghfiroh; Sisca Galuh Setyorini; Puteri Nursyahira Qistina binti Dzulkiflee (Al-Muhasib: Journal of Islamic Accounting and Finance, 2025)
Abstract: This study analyzes the implementation of Financial Accounting Standard (PSAK) 109 in Zakat, Infaq, and Sadaqah (ZIS) accounting at the National Zakat Agency (BAZNAS) of Kediri Regency using a qualitative case study approach with data triangulation: in-depth interviews with 8 managers (including chairperson and staff), observation of accounting processes, and analysis of 2024 financial reports and program archives. Findings reveal structured standard implementation across three dimensions: (1) Cash-based revenue recognition (zakat recognized upon receipt), (2) Transaction classification by fund type (ZIS/grants) and asnaf (8 beneficiary groups), (3) Segregation of amil funds (12.5% zakat; 20% infaq) following sharia principles. Transparency evidence is demonstrated through detailed fund collection (IDR 8.20 billion), distribution (IDR 6.12 billion), and differentiated balances (operational: IDR 1.11 billion; grants: IDR 9.13 million), with 63% of ZIS funds allocated to empowerment programs (Kediri Berdaya, Kediri Cerdas). Key challenges include reporting inconsistencies from 40% of Zakat Collection Units (UPZ) and human resource limitations in applying complex PSAK 109 clauses (e.g., productive waqf measurement). This study provides the first empirical model of PSAK 109 implementation at the regency level, integrating sharia-accounting compliance, with practical implications for replicating this reporting structure across 514 BAZNAS/Lazis institutions in Indonesia to enhance accountability and accelerate poverty alleviation.Abstract: Penelitian ini menganalisis implementasi PSAK 109 dalam akuntansi ZIS di BAZNAS Kabupaten Kediri melalui pendekatan studi kasus kualitatif dengan metode triangulasi data: wawancara mendalam terhadap 8 pengelola (termasuk ketua dan staf), observasi proses akuntansi, serta analisis dokumen laporan keuangan 2024 dan arsip program. Temuan mengungkap penerapan standar terstruktur dalam tiga dimensi: (1) Pengakuan pendapatan berbasis kas (zakat diakui saat diterima), (2) Klasifikasi transaksi berdasarkan jenis dana (ZIS/hibah) dan asnaf (8 golongan mustahik), serta (3) Pemisahan akun hak amil (12,5% zakat; 20% infak) sesuai syariah. Bukti transparansi tercermin dari rekapitulasi rinci pengumpulan dana (Rp8,20 miliar), distribusi (Rp6,12 miliar), dan saldo terdiferensiasi (operasional Rp1,11 miliar; hibah Rp9,13 juta), dengan 63% dana ZIS dialokasikan ke program pemberdayaan (Kediri Berdaya, Kediri Cerdas). Tantangan utama meliputi inkonsistensi pelaporan dari 40% UPZ dan keterbatasan SDM dalam penerapan PSAK 109 ayat kompleks (e.g., pengukuran wakaf produktif). Studi ini menyediakan model empiris pertama implementasi PSAK 109 di tingkat kabupaten yang mengintegrasikan kepatuhan syariah-akuntansi, dengan implikasi praktis berupa potensi replikasi struktur pelaporan ini oleh 514 BAZNAS/LAZ se-Indonesia untuk meningkatkan akuntabilitas dan percepatan pengentasan kemiskinan.